Stability of developing oil companies of Russia - V. V. Biryukova (Вестник СибАДИ, 2017)
In the article the questions of stability of developing Russian companies of an oil and gas complex are considered; methodological and methodical approaches to the analysis of stability of the oil companies as difficult, open spontaneous social and economic systems are stated; results of the stability assessment of their development on the basis of determining indexes of economic efficiency, ecological and social responsibility, and also innovative activity are presented.